Strategi Integrated Marketing Communication (IMC) Sekolah Musik Indonesia sebagai Sekolah Musik Berbasis Teknologi - Christina Nur Wijayanti (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
The purpose of this research is to describe the Integrated Marketing Communication (IMC) strategy carried out by the Sekolah Musik Indonesia (SMI) as a technology-based music school. The research is wualitative research. The research uses interview, observation, and study of documents method to collect data. From the finding of the data obtained, the researcher concludes that the Integrated Marketing Communication (IMC) strategy carried out by SMI combines several forms of promotional mix but with one purpose of introducing and attracting the public to be interested in joining as students at SMI. Some forms of promotion carried out are public relations, direct marketing, sales promotion, personal selling, and advertising.